2015
DOI: 10.4187/respcare.03309
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Interfaces on Synchrony During Pressure Support Ventilation in a Pediatric Setting: A Bench Study

Abstract: BACKGROUND: In adults and children, patient-ventilator synchrony is strongly dependent on both the ventilator settings and interface used in applying positive pressure to the airway. The aim of this bench study was to determine whether different interfaces and ventilator settings may influence patient-ventilator interaction in pediatric models of normal and mixed obstructive and restrictive respiratory conditions. METHODS: A test lung, connected to a pediatric mannequin using different interfaces (endotracheal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 30 publications
0
22
0
1
Order By: Relevance
“…Face‐mask is the first choice interface to provide non‐invasive ventilation in bigger children and adults . NHFOV has never been studied on clinical ground using interfaces other than nasal prongs or in patients beyond neonatal age.…”
Section: Introductionmentioning
confidence: 99%
“…Face‐mask is the first choice interface to provide non‐invasive ventilation in bigger children and adults . NHFOV has never been studied on clinical ground using interfaces other than nasal prongs or in patients beyond neonatal age.…”
Section: Introductionmentioning
confidence: 99%
“…Wolfler et al include NIV guidelines in their cohort national study, stating that helmets are an optimal CPAP interface. A bench study in a pediatric setting suggested that helmets might offer significantly worse patient‐ventilator synchrony during non‐invasive pressure support ventilation when compared to the face mask, but these authors used a standard ICU ventilator without the air leak compensation software on, which might have contributed to their results …”
Section: Discussionmentioning
confidence: 99%
“…A recent bench study [22] evaluated how different interfaces and ventilator settings may influence patient-ventilator interaction in pediatric models of normal and mixed obstructive and restrictive respiratory conditions. A test lung, connected to a pediatric mannequin using an endotracheal tube, a face mask, and a helmet, was ventilated in PSV, testing different ventilator settings, randomly applied.…”
Section: Noninvasive Ventilation In Pediatric Icumentioning
confidence: 99%